Strategies to Mitigate the Effects of Negative Political Rhetoric on Service Providers: A Study in Two Refugee-serving Organizations. Issue 2 (15th March 2022) - Wathen, Maria V.; Weishar, Charity N.; Decker, Patrick L.F.
ABSTRACT: This paper explores the strategies that staff at two refugee-serving organizations found helpful in mitigating their increased distress from negative political rhetoric aimed at their clients. Results point to the importance of organizational acknowledgment of the distress. Additionally, staff perceived that intentionally focused organizational interventions can mitigate the emotional impacts of negative rhetoric. Finally, strategies employees used to lessen their distress and regain a sense of efficacy included recommitment to the mission, advocacy for refugees among family and friends, strong reliance on religious faith in coping, and an avoidance of the rhetoric by decreasing engagement with news and social media.